A Aplikasi Bulu Digital Inovasi E-government untuk Peningkatan Aksebilitas dan Kecepatan Pelayanan Pembuatan Surat Desa - Yogi Noviana, Ovie; Mauliditya Valencia Yolanda, Regina; M. Nazyd Mavaza; Ceisa Santi, Nirma (Management of Information System Journal, 2025)
The development of the Bulu Digital application represents an innovation to support the e-Government Smart Village concept in Bulu Village, Bojonegoro Regency, East Java. This application is designed to facilitate digital administrative processes, enhancing efficiency, transparency, and accessibility of public services for residents. The approach employed includes participatory methods, Agile, and SDLC, involving community members and village officials through observation, interviews, and group discussions. The application enables residents to submit applications online, monitor their status, and manage digital archives that are secure and well-organized. In addition to accelerating service delivery and reducing the risk of document loss, this digital implementation also promotes technological literacy among villagers, thus accelerating the transition toward a self-reliant and modern village. This innovation is expected to serve as a model for other villages in utilizing technology to improve.